Evaluation of methodologies for equine biometry - dos Santos M.R.* (2017)
© 2017 Elsevier B.V.Equines have some peculiarities of zootechnical interests that differ from other species, mainly due to their motor capacity to perform work or sporting functions. For that reason, body dimensions and proportions are extremely important in horse selection and breeding, and morphological characteristics such as length, height, width and angular measurements may influence the quality of movement and physical structure of the animal. In this way, this work aimed to evaluate the biometric data of equines, obtained by the traditional method of body measurement and photogrammetry technique using ImageJ® software. In addition, the methods were correlated and the limitations and advantages of each one were shown. The effect of evaluators for both methods was verified to demonstrate the efficiency of the procedures. Three trained evaluators took body measurements, each performing four replications per horse. A total of 10,944 biometric measurements were taken on twenty-four adult horses. The data was collected from 19 biometric measurements, and photographic images were captured with the purpose of performing measurements in these same anatomical points through the software. The results of this work demonstrated that there is a very high correlation between biometric measurements and photogrammetry for four metric measurements with values between 0.90 and 0.95 and for six measures of high correlation (0.73–0.86). Angular measurements showed the largest differences, with correlations ranging from negligible to high (0.29–0.81). It was concluded that the ImageJ® software is an alternative that can be used to obtain equine morphological data, due to the easy execution of data collection, as well as the fact that the software is free. Thus, this strategy can be used mainly by breeders who seek to form a database with zoometric information that is essential for equine genetic improvement.